Cascaded lattice Boltzmann method for incompressible thermal flows with heat sources and general thermal boundary conditions. (30th March 2018) - Fei, Linlin; Luo, Kai Hong
Highlights: A central-moment scheme is proposed to incorporate heat sources into the CLBM. A general bounce-back scheme is employed to implement thermal boundaries in CLBM. The proposed methods are tested by several benchmarks, showing excellent accuracy. Abstract: Cascaded or central-moment-based lattice Boltzmann method (CLBM) is a relatively recent development in the LBM community, which has better numerical stability and naturally achieves better Galilean invariance for a specified lattice compared with the classical single-relation-time (SRT) LBM. Recently, CLBM has been extended to simulate thermal flows based on the double-distribution-function (DDF) approach [L. Fei et al., Int. J. Heat Mass Transfer 120, 624 (2018)]. In this work, CLBM is further extended to simulate thermal flows involving complex thermal boundary conditions and/or a heat source. Particularly, a discrete source term in the central-moment space is proposed to include a heat source, and a general bounce-back scheme is employed to implement thermal boundary conditions. The numerical results for several canonical problems are in good agreement with the analytical solutions and/or numerical results in the literature, which verifies the present CLBM implementation for thermal flows.